Recent advances (2018–2023) and research opportunities in the study of groundwater in cold regions - Lemieux, Jean-Michel; Frampton, Andrew; Fortier, Philippe (Permafrost and Periglacial Processes, 2025)
Increasing greenhouse gas levels drive extensive changes in Arctic and cold- dominated environments, leading to a warmer, more humid, and variable climate. Associated permafrost thaw creates new groundwater flow paths in cold regions that are causing unprecedented environmental changes. This review of recent advances in groundwater research in cold environments has revealed that a new paradigm is emerging where groundwater is at the center of these changes. Groundwater flow and associated heat and solute transport are now used as a basis to understand hydrological changes, permafrost dynamics, water quality, integrity of infrastructure along with ecological impacts. Although major advances have been achieved in cold regions' cryohydrogeological research, the remaining knowledge gaps are numerous. For example, groundwater as a drinking water source is poorly documented despite its social importance. Lateral transport processes for carbon and contaminants are still inadequately understood. Numerical models are improving, but the highly complex physical- ecological changes occurring in the arctic involve coupled thermal, hydrological, hydrogeological, mechanical, and geochemical processes that are difficult to represent and hamper quantitative analysis and limit predictive capacity. Systematic long- term observatories where measurements involving groundwater are considered central are needed to help resolve these research gaps. Innovative transdisciplinary research will be critical to comprehend and predict these complex transformations.